Pengembangan Model Pembelajaran Whole Languege Untuk Menumbuh Kembangkan Kemampuan Berbahasa Tulis Siswa Sekolah Dasar - Halimah, Lely; Syahrudin, Didin; Abidin, Yunus (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2011)
AbstractSome mistake are finding in teaching and learning language at the schools until today. This condition happened because there is some mistake in teaching and learning language at the schools. Because of that, the process of teaching and learning literature at schools must be change by using the effective models of teaching and learning language which can improve student literacy. One of the models for teaching and learning literacy is Whole Language Model. The problems of this research are (1) what is real condition of learning and teaching language process in the schools? (2) how to development whole language models which can improve student’s literacy? (3) are there influence in using whole language model toward student’s literacy improvement? .Method of this research is research and development. The subject of this research is student in Primary School Laboratory UPI Cibiru Campus. Measurement utilizes test and observation. The statistic analysis technique is using to analysis the date. Result of this research concludes that (1) teacher needs the good model of learning and teaching language to improving student’s literacy in the school; (2) whole language model can implementating by three step that is introduction step, process step, and closing step; (3) implementation of whole language model of teaching and learning language can improving student’s literacy in the primary school.Key Word: Whole Language, Elementary Student, Literacy